PD-1 and PD-L1 immune checkpoint blockade to treat breast cancer - Hartkopf, Andreas; Taran, Florin-Andrei; Wallwiener, Markus; Walter, Christina B.; Krämer, Bernhard; Grischke, Eva-Maria; Brucker, Sara Y. (Breast care, 2016)
Immune checkpoint inhibition represents a major recent breakthrough in the treatment of malignant diseases including breast cancer. Blocking the programmed death receptor-1 (PD-1) and its ligand, PD-L1, has shown impressive antitumor activity and may lead to durable long-term disease control, especially in the triple-negative subtypes of breast cancer (TNBC). Although immune checkpoint blockade is generally well tolerated, specific immune-related adverse events (irAEs) may occur. This review summarizes the clinical efficacy, perspectives, and future challenges of using PD-1/PD-L1-directed antibodies in the treatment of breast cancer.